KAJIAN PERUBAHAN EROSI PERMUKAAN AKIBAT PEMBANGUNAN HUTAN TANAMAN INDUSTRI DI AREAL PENCADANGAN HTI KABUPATEN KETAPANG PROPINSI KALIMANTAN BARAT - Saptarini N., C. Lestari; A. Kironoto, Bambang; Jayadi, Rachmad (Civil Engineering Forum Teknik Sipil, 2007)
Allocated area for planted-forest in Ketapang Regency, especially in Durian Sebatang river basin and its surrounding are in critical condition with low land- productivity and poor hydrologic characteristic. These areas have to be conserved with vegetative method. One of the efforts to synergize soil and water conservation and economic interest is immediately to rehabilitate the critical areas with Planted-Forest (Hutan Tanaman Industri—HTI). Planted-forest system can be arranged to control the rate of erosion. The aim of this study is to predict the rate of erosion at the existing condition and the change of erosion rate at the planting-rotation system (cutting system) in the planted-forest of Acacia sp. The planting- rotations are 5 years, 6 years, 7 years and 8 years during the range of 11 years study. The research uses the version 3.3 of GIS Arc View program to make the land-unit map. The amount of surface erosion (sheet erosion) estimated base on the land-unit map. The calculation of the erosion rate uses the Modified USLE method (Snyder,1989), in which factors influencing the amount of surface erosion are Rain Erosivity (R), Land Erodibility (K), Length and Elevation of slope (LS) and Soil Conservation Factor and Planting System (VM). The results of the study show that the rate of erosion at the existing condition is 1,24 mm/year. Its a light danger erosion level, under the soil loss tolerance limits (2 mm/year). During the 11 first years of HTI development, the rate of erosion in planted forest with planting rotation of 5, 6, 7 and 8 years ranges from 0,91 mm/year to 2,66 mm/year. Its included in a very light to heavy erosion danger level. The lowest average erosion rate is found in the planting rotation of 7 year, continued by 8, 6 and 5 year. At first cycle, the rates of erosion in all planting rotation are more than the amount of existing erosion. Its caused by land clearing activity for plantation, but at further cycle, those are decrease until under the existing condition when the vegetation at conservation areas reach to an optimal growth. The rates of erosion in HTI can be controlled if we arrange the allocation of land utilization t consider by soil type. The reasonable planting-rotation of HTI with Acacia sp vegetation’s type to be applied in the research area is 6 years or 7 years. The optimal planting rotation is decided base on amount of erosion rate, soil stability, wood utilization and economic value. The expectation of this research can be contribute in soil conservation and social economic integrated development program.